Assessment of ammonium-based solutions (ABS) AS Aedes aegypti OVIPOSITION ATTRACTANT - Mohd Farihan Md Yatim,; Faizul Akmal Abdul Rahim,; Mohd Amierul Fikri Mahmud,; As'malia Md Lasim,; Aishah Hani Azil, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Aedes aegypti exhibit a higher preference for ovipositing their eggs in water that possess with dissolved mineral and nutrient for the survival of their progeny. These solutions usually contain ammonia which was formed due to decomposing process of decaying organic matter in the water. Therefore, the understanding of oviposition preferences is crucial for developing effective strategies in vector control programme. The attractiveness of aqueous ammonia, ammonium nitrate and a mixture of ammonium and acid lactic to gravid Ae. aegypti were accessed through dual and multiple choice bioassays under laboratory conditions. In dual and multiple choice bioassays, female mosquitoes was highly tend to oviposit their eggs in the mixture of ammonium and acid lactic solution (152.87±11.06) compared to the ammonium nitrate (134.13±10.32)) and ammonium aqueos (141.60±11.93). Solution of ammonium nitrate was less effective to attract gravid Aedes in dual bioassays’ studies (P>0.05). This finding indicates that the combination of ammonium and acid lactic could be used in ovitrap surveillance programme. However, further research on combination of ammonium and acid lactic is warranted to find a better oviposition attractant for Ae. aegypti.